2009
DOI: 10.1111/j.1365-2133.2008.08826.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic features of melanomas associated withMC1Rvariants in SpanishCDKN2Amutation carriers

Abstract: Early melanomas in patients with two MC1R red hair variants may be difficult to diagnose definitively by dermoscopy because, in our limited experience, they show fewer colours and structures and have a lower TDS. In such melanomas, subtle atypical vessels and other changes detected by digital image follow up may be useful to confirm the diagnosis of melanoma. An integrated approach including clinical history and dermoscopic data (also considering additional information, such as the presence of atypical vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 27 publications
4
55
0
Order By: Relevance
“…A report on the dermoscopic features of primary melanomas in nine high-risk CDKN2A mutation carrier patients from the Spanish population found that the mean ABCD total dermoscopy score was significantly higher in those with MC1R non-RHC genotype (Cuellar et al, 2009) compared with those who carried two MC1R RHC variant alleles. Although the melanomas in CDKN2A patients homozygous for MC1R RHC alleles were more difficult to diagnose, with less color and fewer structures, atypical vessels were observed.…”
Section: Discussionmentioning
confidence: 98%
“…A report on the dermoscopic features of primary melanomas in nine high-risk CDKN2A mutation carrier patients from the Spanish population found that the mean ABCD total dermoscopy score was significantly higher in those with MC1R non-RHC genotype (Cuellar et al, 2009) compared with those who carried two MC1R RHC variant alleles. Although the melanomas in CDKN2A patients homozygous for MC1R RHC alleles were more difficult to diagnose, with less color and fewer structures, atypical vessels were observed.…”
Section: Discussionmentioning
confidence: 98%
“…From our own experience, we are of the opinion that the pigmented lesions in many of these high-risk patients are more difficult to diagnose because many of their benign nevi manifest clinical and/or dermoscopic features of melanoma or their melanomas manifest subtle features that make their detection a challenge. Cuellar et al recently reported that in fair-skinned individuals early melanomas can be difficult to diagnose [20]. Thus, the MelaFind® database is biased towards lesions with a higher degree of diagnostic difficulty as compared to lesions encountered in the setting of a general dermatology office.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may confirm the presence of a correlation between genetic background and the clinical and dermoscopic appearance of melanocytic lesions, as already found in previous studies. In particular, Cuéllar et al [7] evaluated the possibility of a correlation between particular dermoscopic patterns and variants of the MC1R gene, a gene responsible for much of the diversity in human pigmentation due to its important role in determining the ratio of eumelanin and pheomelanin production. They found that the mean ABCD total dermoscopy score of the suspect melanocytic lesions excised was significantly higher in noncarriers of red hair MC1R polymorphisms than in carriers of two MC1R gene red hair variants.…”
Section: Discussionmentioning
confidence: 99%